Model of knowledge transfer through gamification: A gcMooc - Terán Bustamante, Antonia (2019)
In recent years, the MOOC (Massive Open Online Course) is an essential piece of distance education. The aim of this research article to analyze a knowledge transfer model through an entrepreneurial MOOC, where the basis of the course for knowledge creation is creative strategies of learning as gamification, communities of practice. The methodological approach used in this research is mixed, quantitative and qualitative descriptive. The population under study is 1910 people, of which 890 (46.60%) participated at the beginning and 216 (24.3%) finalized, to which it uses two questionnaires. The course structure is connectivism, cooperation, and gamification, with a practical methodology of game-based learning to develop the spirit of enterprise. The results show a higher percentage of student retention through the introduction of an educational scenario design based on games, through visual contents and intellectual challenges. At the same time, the evidence shows that in the realization of this course it is necessary to work on mechanisms of delivery and quality of material must be worked on and presented in short times. The research concluded that the understanding of a MOOC is not an easy task; it involves many pedagogical tools to achieve higher retention.